The role of the knowledge economy in the development of the banking industryAlgeria case study (Numerus academy review, 2026)
This study aimed to highlight the importance of employing the knowledgeeconomy in the banking industry, by addressing its concept, characteristics andemployment in the banking industry, through electronic payment by its means andchannels, while addressing Algeria's efforts in this field.The study concluded that employing the knowledge economy in the bankingindustry has become more than a necessity, especially in light of the exceptional health conditions the world is witnessing, which require more social distancing as a result of thespread of the Corona pandemic, because technology enables access to services remotely.